Digital Literacy Competence Survey in Medan City - Yovita Sabarina Sitepu; Mickhael Rajagukguk (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2022)
This study measures Medan’s level of digital literacy competence. This study aims to obtain an overview of the digital literacy competencies of smartphone users in Medan City. This research was part of the National Digital Literacy Research, initiated by the Network of Digital Literacy Activists (Japelidi), conducted in 18 cities in Indonesia, involving 125 respondents from Medan City, and divided into five age segments. The research used the descriptive quantitative method. As the instrument, the research used ten Components of Japelidi’s Digital Literacy, which are the ability to access, select, understand, analyze, verify, evaluate, distribute, produce, participate, and collaborate. Digital literacy competence in Medan City showed an imbalance between the younger generation and the elderly. This inequality is not only based on age differences alone but also differences in culture and use of technology in each era.